Confronting lepton flavor universality violation in B decays with high-pT tau lepton searches at LHC - Darius A. Faroughy; Admir Greljo; Jernej F. Kamenik (Physics Letters B, 2017)
We confront the indications of lepton flavor universality (LFU) violation observed in semi-tauonic B meson decays with new physics (NP) searches using high pT tau leptons at the LHC. Using effective field theory arguments we correlate possible non-standard contributions to semi-tauonic charged currents with the τ+τ− signature at high energy hadron colliders. Several representative standard model extensions put forward to explain the anomaly are examined in detail: (i) weak triplet of color-neutral vector resonances, (ii) second Higgs doublet and (iii) scalar or (iv) vector leptoquark. We find that, in general, τ+τ− searches pose a serious challenge to NP explanations of the LFU anomaly. Recasting existing 8 TeV and 13 TeV LHC analyses, stringent limits are set on all considered simplified models. Future projections of the τ+τ− constraints as well as caveats in interpreting them within more elaborate models are also discussed.